FACILITATING INDONESIAN PRIMARY SCHOOL’S SPEAKING SKILLS THROUGH THE USE OF SCAVENGER HUNT AND HOPSCOTCH GAMES - Hearlie Agritia Chrishantie; Nunung Nurjati (Magister Scientiae, 2025)
This study examines how well Hopscotch and Scavenger Hunt exercises help Indonesian primary school pupils' speaking abilities. The study collected data using semi-structured interviews, documentary analysis, and observations using a qualitative descriptive design. The findings demonstrated that these exercises greatly enhanced students' speaking skills, which raised their level of satisfaction and self-assurance in their English language study. Nonetheless, problems like low participation rates and linguistic barriers were noted. According to the study's findings, elementary schools can benefit from including interactive games like scavenger hunts and hopscotch into their lesson plans for language acquisition. Their long-term effects and application in other age groups and educational contexts may be investigated in future studies. Keywords: scavenger hunt, hopscotch, speaking skills